Immunogenicity and persistence of a prime-boost re-vaccination strategy for pneumococcal vaccines in patients with rheumatoid arthritis. Issue 6 (3rd June 2018) - Bahuaud, Mathilde; Beaudouin-Bazire, Constance; Husson, Marine; Molto, Anna; Launay, Odile; Batteux, Frédéric; Dougados, Maxime
ABSTRACT: Objectives : Patients with rheumatoid arthritis (RA) are at an increased risk of Pneumococcal infections. Immunogenicity and persistence of a prime-boost revaccination strategy using 13-valent/23-valent anti-pneumococcal vaccines was evaluated in patients with RA treated by Methotrexate (MTX) and anti-TNF. Method : Twenty-four patients with RA received one dose of PCV13 (Prevenar13®; Pfizer) followed two months later by one dose of PPV23 (Pneumovax®, Merck). Concentrations of IgG specific for 7 serotypes common to both vaccines and 3 uncommon serotypes, included only in the PPV23 were measured by ELISA and Opsonophagocytic Assay (OPA) at baseline and after 4, 12 and 24 months post-vaccine. Results : Similar percentages of protection were found at 4 months (63% vs. 55%), 12 months (54% vs. 50%) and 24 months (52% vs. 55%) for the 7 common and 3 uncommon serotypes when antibody titers were assayed by ELISA. Based on functional antibody measurements by OPA, a decrease of protected patients was observed 24 months after vaccine with only 19% of patients protected compared to 29% at baseline. Conclusion : Although the combined pneumococcal revaccination strategy induces good protection in the short term in RA patients, this protection does not persist beyond two years with levels of functional antibody decreasing below pre-vaccine levels. We did not observe a higher efficacy of the conjugate vaccine compared to the polysaccharide vaccine. Our results clearly question the advantage of the prime-boost strategy as it highlight the possible hyporesponse induced by PPV23 against the immune response elicited by the primo-injection of the PCV13 vaccine.